Successful Venous Angioplasty of Superior Vena Cava Syndrome after Heart Transplantation - Thomas Strecker; Iris Zimmermann; Marco Heinz; Johannes Rösch; Abbas Agaimy; Michael Weyand (Case Reports in Cardiology)
Introduction. For patients with terminal heart failure, heart transplantation (HTX) has become an established therapy. Before transplantation there are many repeated measurements with a pulmonary artery catheter (PAC) via the superior vena cava (SVC) necessary. After transplantation, endomyocardial biopsy (EMB) is recommended for routine surveillance of heart transplant rejection again through the SVC. Case Presentation. In this report, we present a HTX patient who developed a SVC syndrome as a possible complication of all these procedures via the SVC. This 35-year-old Caucasian male could be successfully treated by balloon dilatation/angioplasty. Conclusion. The SVC syndrome can lead to pressure increase in the venous system such as edema in the head and the upper part of the body and further serious complications like cerebral bleeding and ischemia, or respiratory problems. Balloon angioplasty and stent implantation are valid methods to treat stenoses of the SVC successfully.